International disability law : a practical approach to the united nations convention on the rights of persons with disabilities - Pyaneandee, Coomara; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2018)
This book provides a concise guide to international disability law. It analyses the case law of the CRPD Committee and other international human rights treaty bodies, and provides commentaries on more than 50 leading cases. The author elaborates on the obligations of States Parties under the CRPD and other international treaties, while also spelling out the rights of persons with disabilities, and the different mechanisms that exist at both domestic and international levels for ensuring that those rights are respected, protected and promoted. The author also delineates the traditional differentiation between civil and political rights on the one hand, and economic, social and cultural rights on the other. He demonstrates, through analysis of the evolving case law, how the gap between these two sets of rights is gradually closing. The result is a powerful tool for political decisionmakers, academics, legal practitioners, law students, persons with disabilities and their representative organisations, human rights activists and general readers.
part PART I General provisions -- chapter 1 Functions of the CRPD Committee -- chapter 2 Pillars of the CRPD -- chapter 3 Women and girls with disabilities -- part PART II Civil and political rights -- chapter 4 Legal capacity and access to justice -- chapter 5 Security of the person -- chapter 6 Right to life -- chapter 7 Participation in political and public life -- part PART III Economic, social and cultural rights -- chapter 8 Accessibility -- chapter 9 Right to education -- chapter 10 Right to work and employment -- chapter 11 Inclusive independent living.
Keywords: Civil rights; Comparative law; Disability Studies - Sociology; Disability studies; Discrimination; Human Rights Law & Civil Liberties; Human rights; International law; Jurisprudence & General Issues; Jurisprudence; Public International Law; Public law; Social policy; Socio-Legal Studies - International Law & Politics; Socio-Legal Studies - Public Policy; World politics; LAW / Comparative; LAW / Constitutional; International law and human rights; People with disabilities -- Legal status, laws, etc